2017
DOI: 10.1097/j.pain.0000000000001144
|View full text |Cite
|
Sign up to set email alerts
|

Are group size and composition associated with treatment outcomes in group cognitive behavioural therapy for chronic pain?

Abstract: This study explored whether group size and group member characteristics (age, sex, and compensation status) were associated with patient outcomes (changes in pain and disability). Retrospective analyses of outcome data obtained from 2 independently run group cognitive behavioural therapy (CBT) programs for chronic pain (Program A: N = 317 and Program B: N = 693) were conducted. Intracluster correlations were significant in both studies, indicating group-level effects on patient outcomes in both group CBT progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…We have previously identified features of group size, age and gender mix, as well as the mix of compensable patients that are associated with outcomes. 7 We have now identified that in two CBT-based pain management programmes that varied in intensity, duration, patient characteristics and certain content, the median baseline scores of catastrophising, depression and fear of movement for a group were not associated with pain-related outcomes. That is, our results suggest that there is no systematic difference in outcomes across the group according to their collective profile when they start.…”
Section: Limitations and Future Directionsmentioning
confidence: 95%
See 2 more Smart Citations
“…We have previously identified features of group size, age and gender mix, as well as the mix of compensable patients that are associated with outcomes. 7 We have now identified that in two CBT-based pain management programmes that varied in intensity, duration, patient characteristics and certain content, the median baseline scores of catastrophising, depression and fear of movement for a group were not associated with pain-related outcomes. That is, our results suggest that there is no systematic difference in outcomes across the group according to their collective profile when they start.…”
Section: Limitations and Future Directionsmentioning
confidence: 95%
“…For further details of the programme, refer to Nicholas et al 20 Separate data from these participants had been used to test the effect of adherence to self-management strategies 21 and a study on group composition. 7…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The independent variables were group size and group composition in terms of gender, ethnicity and disability benefits status, and baseline pain intensity and interference, depression, pain acceptance and stigma. The independent group composition variables were selected to replicate and extend elements of the previous work of Wilson et al, 19,20 as discussed. We hypothesised that these variables would be associated with the post-treatment individual level outcomes of pain intensity, pain interference, and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Empirically, however, there is a lack of evidence to suggest that individuals fare better in groups where other families have similar ethnic and educational backgrounds. The feeling of being similar to others provides a basis for relationship building, increasing group identification, and commitment to group goals (Wilson et al, 2018). However, grouping families based on ethnic or educational backgrounds may risk parents to feel stereotyped, and normalizing experiences may be greater when families see that families with different backgrounds experience similar problems (Mørch et al, 2004).…”
mentioning
confidence: 99%